Correlation of field and experimental test data of wear in heavy commercial vehicle brake liners - B. Surya Rajan; M. A. Sai Balaji; C. Velmurugan (Friction)
Abstract The correlation between the wear behavior of a heavy commercial vehicle (HCV) brake liner tested under controlled laboratory conditions and that in actual field conditions is investigated. A brake liner study for friction and wear is performed on an inertia brake dynamometer (IBD) at different temperatures (200 °C, 250 °C, and 300 °C) using 6000 brake actuations in a laboratory. The total wear loss of the brake liner at three different temperatures for 6000 brake actuations in IBD is found to be 1.12 mm. The actual field test is conducted on four different HCVs, namely, a city bus (CB), a high speed bus (HSB), a highway truck (HWT), and a tipper lorry (TL). These HCVs run at different terrain/traffic conditions and load conditions. When comparing the predicted life of the brake liner through the IBD test with the actual life of the brake liner in different HCVs, a vast difference is observed. Due to the large variation of liner life observed between the actual and predicted tests, an extensive field test is conducted. In the field test, the liner with identical formulation is fitted in the four types of HCVs. The predicted life of the liner using IBD is then correlated with the field test observation and a correlation factor is determined. Based on this correlation factor, the predicted life of the liner and the achieved life on the HCV are found to be fairly close. This study will be useful to design the friction material formulation and to predict the actual life of the brake liner for various HCVs.